Tinjauan Pustaka: Peran Permainan Ranjau Sepatu dalam Strategi Pembelajaran untuk Meningkatkan Kerjasama Siswa SD - Diprono, Arjun Naja Abrori Cokro; Siswanto, Yuli; Adiyanto, Rizky (Universitas Sebelas Maret, 2025)
Collaboration is a crucial 21st-century skill that should be nurtured from an early age. Traditional instructional methods often lack opportunities to develop students’ collaborative competencies effectively. Therefore, innovative and engaging strategies are needed to foster positive social interaction and support character education in elementary schools. This literature review explores the potential of the